THE INFLUENCE OF FIRM SIZE, LEVERAGE, PROFITABILITY, AND DIVIDEND POLICY ON FIRM VALUE OF COMPANIES IN INDONESIA STOCK EXCHANGE - Prasetya Margono, Ferdy; Gantino, Rilla (Copernican Journal of Finance & Accounting, 2021)
The aim of this study is to acquire empirical proof on the impact of firm size, leverage, profitability, and dividend policy on the firm value of the consumer goods industry in the food & beverage sub-sector listed on IDX in 2016-2019. Firm size is calculated by Ln of total sales, leverage is calculated by the Debt to Assets Ratio (DAR), profitability is calculated by Return On Equity (ROE), dividend policy is calculated by Dividend Payout Ratio (DPR), and firm value is calculated by Price to Book Value (PBV). The methodology used purposive sampling. The number of samples used in this research were 10 consumer goods industry companies in the food and beverage sub-sector listed on the IDX during 2016-2019. The data source of this research comes from the company’s yearly financial reports. This research uses a quantitative oncoming with multiple linear regression analysis methods. The resumes of this research found that firm size, leverage, profitability, and dividend policy simultaneously influence firm value; firm size has no impact on company value; leverage has a positive impact on company value; profitability has a positive impact on company value; and dividend policy has a positive impact on company value.